Analisis Pengetahuan Gizi dan Pendidikan Kesehatan pada Remaja - Annisa Nursita Angesti; Ratna Mutu Manikam; Ratih Agustin Prikhatina; Afifah Nanda Tifani (Jurnal Inovasi Pendidikan MH Thamrin, 2022)
Nutritional status as an adult can be determined by eating patterns during adolescence. One of the factors that influence eating patterns is nutritional knowledge and snack habits, because at that age, teenagers spend a lot of time at school. Snacking habits in adolescents that are high in calories can lead to overweight and obesity. Health Education important to students for prevent disases case by poor nutrition/overweight. This study aims to determine the relationship between nutritional knowledge and eating habits in adolescents at Senior High School (SMA) Budhi Warman 1 in 2022. The design of the study used a cross-sectional study with 184 respondents aged 15-17 years. The data collection technique used was simple random sampling with instruments in the form of self-data questionnaires and snack habits. The data analysis used was univariate and bivariate with the chi-square test. There are 71.2% of female adolescents and 28.8% of male adolescents. The results of the analysis show that there is a relationship between the frequency of snacks (p value 0.003), the reason for the snacks (p value 0.002), the type of snack food (p value 0.002) and the drink of snacks (p value 0.011) with gender. Nutrition education, especially regarding choosing healthy snacks, must still be given to adolescents so that students can choose snacks that are good for nutrition and health.